2022
DOI: 10.1002/aenm.202103702
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Volatile Perfluorophenyl‐Based Additive for Enhanced Efficiency and Thermal Stability of Nonfullerene Organic Solar Cells via Supramolecular Fluorinated Interactions

Abstract: A novel non‐volatile additive, fluorinated bis(perfluorophenyl)pimelate (BF7), is demonstrated to effectively improve both the efficiency and thermal stability of a highly efficient organic solar cell (OSC), comprising fluorinated Y6 as the small‐molecule acceptor and PM6 as the polymer donor. Processed with optimized 0.5 wt% BF7 in solution, the PM6:Y6:BF7 device achieves an elevated power conversion efficiency (PCE) of 17.01%, compared to 15.16% of that processed without BF7. Moreover, the BF7‐elevated PCE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…In addition to the photo-oxidation and photocatalyzed nucleophilic reactions that tend to break the NFA’s conjugation to degrade their light absorbing capabilities 20 23 , the relationship between their chemical structures and the morphological evolution under external stresses also needs to be concerned. Thermal stress induced instability is a very challenging problem for OPV 24 , because the best-performing BHJ devices are often achieved when the active layer morphology is in the thermodynamically non-equilibrated state 24 , which needs to be maintained during the whole thermal aging process. This can be potentially accomplished by tailoring the backbone planarity and side-group hinderance of NFAs, since these structure features are directly related to the crystallization and diffusion abilities of NFAs and their interactions with polymer matrix 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the photo-oxidation and photocatalyzed nucleophilic reactions that tend to break the NFA’s conjugation to degrade their light absorbing capabilities 20 23 , the relationship between their chemical structures and the morphological evolution under external stresses also needs to be concerned. Thermal stress induced instability is a very challenging problem for OPV 24 , because the best-performing BHJ devices are often achieved when the active layer morphology is in the thermodynamically non-equilibrated state 24 , which needs to be maintained during the whole thermal aging process. This can be potentially accomplished by tailoring the backbone planarity and side-group hinderance of NFAs, since these structure features are directly related to the crystallization and diffusion abilities of NFAs and their interactions with polymer matrix 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The energy loss ( E loss ) of all the optimized active layer OSC devices are calculated according to the relation of E loss = E g – qV oc . The bandgap is estimated from the intersection of normalized PL emission and UV–vis absorption spectra of D/A blend in film state, as depicted in Figure S3 . The estimated E loss of PBDB-T:TPQ-eC7-4F-, PBDB-T:TPQ-eC7-4Cl-, and PBDB-T:BTP-eC7-4Cl-based optimized OSC devices are 0.593, 0.596, and 0.691, respectively (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Temperature-dependent GIWAXS conducted for the PM6:Y6 device films without and with the 1.0 wt % 8OC 60 Me additive further revealed that the additive effects on the greatly enhanced long-term stability of the device performance (Figure 2e,f). As shown in Figure 4a,b, the convoluted peak centered at q ≈ 0.32 Å −1 , contributed by both Y6 and PM6 ordered nanodomains, in the out-of-plane or inplane direction, 29 changes the peak intensity and position, as temperature elevated from 30 to 80 °C and to 100 °C. The change of the peak positions was attributed to an enhanced phase separation between PM6 and Y6, as suggested in a previous report, 29 which results in an over phase-separation morphology to the device performance.…”
Section: Evaluation Of Indoor Applicationmentioning
confidence: 94%
“…0.3 Å −1 , which is attributed to the liquid-crystallike, weakly ordered PM6 layering structure, as most of the reflections of Y6 crystallites are largely oriented. 29 Moreover, the characteristic packing peak at q = 1.4 Å −1 (d spacing = 4.49 Å) of the aggregated 8OC 60 Me additive (Figure S16) was not observed in the GIWAXS pattern of the PM6:Y6 with the additive, suggesting that the additive could be effectively dispersed throughout the thin film.…”
Section: Evaluation Of Indoor Applicationmentioning
confidence: 98%